Begonia pulchrifolia (sect. Platycentrum), a new species of Begoniaceae from Sichuan of China - Tian, Dai-Ke; Li, Chun; Li, Ce-Hong; Li, Xiao-Jie (Phytotaxa, 2015)
Begonia pulchrifolia D.K.Tian & C.H.Li, a new species in Begonia sect. Platycentrum A.DC. (Begoniaceae) from Sichuan of China, is described and illustrated. Morphologically, it is only similar to the young or smaller individuals of B. dielsiana and B. emeiensis in plant shape and some leaf characters but differs easily by its foliage color and deeper divided leaf lobes, small-sized flowers, hairy outer petals of the male flowers, and long abaxially winged fruits. Molecular phylogenetic analysis based on nrDNA also supported the distinction of B. pulchrifolia from B. dielsiana and B. emeiensis.